W 100-lecie dekretu o archiwach. Archiwum Państwowe w Bydgoszczy - dzieje i zasób (Kronika Bydgoska, 2018)
The decree of February 7, 1919 on organization of the national archives and care for valuable documents specified the principles for establishing the archive network and functioning of the national archives in interwar Poland. The latter ones were assigned to the Department of the National Archives in MWRiOP. The decree also specified the main tasks of the Department and the national archives. One of them is the National Archives in Bydgoszcz, which origins date back to 1906. Initially, it was the archive of the General Commission in Bydgoszcz, becoming the national archives in 1924. These days it is one of the biggest in the country.